Investigation of the selective catalytic reduction of NO with NH3 over the WO3/Ce0.68Zr0.32O2 catalyst: the role of H2O in SO2 inhibition. (15th January 2019) - Liu, Shuang; Feng, Xi; Liu, Jingying; Lin, Qingjin; Xiong, Lei; Wang, Yun; Xu, Haidi; Wang, Jianli; Chen, Yaoqiang
Abstract : The effect of H2 O and SO2 on the selective catalytic reduction of NO x by NH3 (NH3 -SCR) over WO3 /Ce0.68 Zr0.32 O2 at 250 °C was systematically investigated using various characterization techniques. Abstract : The effect of H2 O and SO2 on the selective catalytic reduction of NO x by NH3 (NH3 -SCR) over WO3 /Ce0.68 Zr0.32 O2 at 250 °C was systematically investigated using various characterization techniques. NH3 -SCR activity revealed that H2 O in the reaction gas had little impact on the NO x conversion at 250 °C, whereas, the presence of SO2 slowly decreased the NO x conversion from 99.6% to 85.0% in 40 h. Particularly, the NO x conversion linearly declined to 75% with the co-existence of SO2 and H2 O in 16 h. Thus, the presence of H2 O obviously accelerated the deactivation of WO3 /Ce0.68 Zr0.32 O2 compared with only the presence of SO2 under NH3 -SCR conditions. Nevertheless, the above deactivation resulting from SO2 and H2 O could be mostly eliminated by thermal treatment. The characterization via XRD, NO/CO2 -TPD, XPS, H2 -TPR, OSC and ex / in situ DRIFT demonstrated that (NH4 )2 SO4 and Ce2 (SO4 )3 were deposited on the surface of the sulfated catalysts, which decreased the number of active sites and weakened the redox properties of WO3 /Ce0.68 Zr0.32 O2 ; thus, resulting in the deactivation of the WO3 /Ce0.68 Zr0.32 O2 catalyst. Importantly, the presence of H2 O accelerated the generation of sulfates on the surface of WO3 /Ce0.68 Zr0.32 O2, which led to the serious deactivation of the catalyst in the presence of both H2 O and SO2 . As a result, the Langmuir–Hinshelwood route of NH3 -SCR over the catalyst was disrupted due to the shielding of sulfate species.